306 INTRAUTERINE GROWTH RESTRICTION DECREASES IMMATURE T CELLS IN THE THYMUS OF JUVENILE RATS. (1st January 2006) - Jenkins, S.; McKnight, R.; Enioutina, E. Y.; Yu, X.; Hale, M. A.; Daynes, R.; Lane, R.
Abstract : Background: IUGR infants have qualitative and quantitative abnormalities in lymphocyte function that persist into childhood, resulting in increased susceptibility to infections. We have previously shown in a rat model of IUGR that there is a decrease in the overall number of lymphocytes. However, little detail is known about the extent to which IUGR affects all white blood cells. Interestingly, lymphocyte phenotype can be altered by high glucocorticoid levels, which also characterizes both IUGR human and rat. Objective: We hypothesized that IUGR affects leukocyte phenotype in postnatal juvenile IUGR rats. Design/Methods: To prove this hypothesis, we used bilateral uterine artery ligation and sham surgery to produce IUGR and control rats ( n = 4 in each group). Perinatal glucocorticoid levels are elevated in this model of IUGR (Baserga et al, AJP, 2005). Pups were allowed to deliver, and litters were culled to 6. Pups were killed on day of life 21, and thymus and spleen were harvested. Organ weight and total cell number were corrected for body weight differences. Monoclonal antibodies and flow cytometry analysis were used to compare the major leukocyte cell lines in the thymus and spleen from 21-day-old juvenile rats. Cells were stained with cell-surface markers for general T cells (CD3 + ), T-helper (CD4 + ), T-cytotoxic (CD8 + ), granulocytes (GR1 + ), B cells (CD45r + ), macrophages (Mac1 + ), and dendritic cells (CD11c + ). Results: Thymus and spleen weights were disproportionately decreased in IUGR. IUGR decreased double positive (CD4 +, CD8 + ) naïve, undifferentiated T cells in the thymus versus controls (72 ± 1% vs 66 ± 1%, p < .05). Additionally, IUGR increased the percentage of more mature, cytotoxic T cells, dendritic and B cells in the thymus. Similarly, the IUGR spleen had a significant shift toward a more mature and cytotoxic phenotype. Conclusions: We conclude that IUGR disproportionately decreases the naïve, undifferentiated T cells in the postnatal thymus and shifts the percentage of cells to a more mature, differentiated phenotype. This is very intriguing because increased glucocorticoid levels have been previously shown to similarly affect lymphocyte phenotype. We speculate that elevated perinatal glucocorticoid levels lead to a persistent change in the postnatal lymphocyte population in the IUGR rat, which represents a pathway through which IUGR causes qualitative and quantitative abnormities in lymphocyte function. Supported by the Children's Health Research Center.